Environmental Exposure to Breast Cancer: Study Narrative Review, How to Prevent in Indonesia? - Elanda Fikri; Yura Witsqa Firmansyah; Muhammad Fadli Ramadhansyah; Wahyu Widyantoro; Aziz Yulianto Pratama; Ayu Widyawati; Ike Rachmawati; Muslyana Muslyana; Ramadani Sukaningtyas; Danang Hendrawan; Khaira Ilma; Hanung Nurany; Maurend Yayank Lewinsca; Rafika Rafika; Laliyanto Laliyanto (Universitas Aisyah Pringsewu, 2021)
The environment is one of the factors in the epidemiological triad as the concept of the emergence of a disease, including breast cancer which is the global burden. Globally, WHO declared breast cancer to have 2.26 million new cases per year in 2020, with the mortality rate climbing to 685,000. In Indonesia, breast cancer has the highest incidence rate for women, with 1.4 per 1000 population in 2013 growing to 1.79 per 1000 people in 2018. This review aims to describe environmental exposure factors that have the potential to cause breast cancer. The review study used the narrative review method with a screening process of 28 articles used. Environmental exposures that become potential occurrences of breast cancer are divided into 4, exposure to pesticides, exposure to household chemicals, exposure to food packaging, and exposure to air pollution which have different pathophysiologies for each exposure. Exposure to chemicals such as DDE and DDT in pesticides that have been proven to be carcinogenic and are still used in Indonesia. Exposure to chemicals from household chemicals such as PCBs, Benzophenone, and Phthalates in some household appliances are also carcinogenic substances. The use of BPA, BaP, and 2-Amino-1-Methyl-6-Phenylimidazo [4,5-B] pyridine in food packaging trigger breast cancer. Exposure to cigarette smoke or smoking behavior, consumption and evaporation of alcohol, as well as exposure to PM2.5 are air pollutants that are at risk of causing breast cancer. How to prevent it, we can use biopesticide, bioplastic, change a healthy lifestyle and replace fossil fuels into biofuels. Abstrak: Lingkungan merupakan salah satu faktor dalam triad epidemiologi sebagai konsep munculnya suatu penyakit, termasuk kanker payudara yang menjadi beban global. Secara global, WHO menyatakan kanker payudara memiliki 2,26 juta kasus baru per tahun pada tahun 2020, dengan angka kematian meningkat menjadi 685.000. Di Indonesia, kanker payudara memiliki angka kejadian tertinggi pada wanita, dengan 1,4 per 1000 penduduk pada tahun 2013 tumbuh menjadi 1,79 per 1000 orang pada tahun 2018. Tinjauan ini bertujuan untuk mendeskripsikan faktor paparan lingkungan yang berpotensi menyebabkan kanker payudara. Kajian review menggunakan metode narrative review dengan proses screening sebanyak 28 artikel yang digunakan. Paparan lingkungan yang menjadi potensi terjadinya kanker payudara dibagi menjadi 4, paparan pestisida, paparan bahan kimia rumah tangga, paparan kemasan makanan, dan paparan polusi udara yang memiliki patofisiologi yang berbeda untuk setiap paparan. Paparan bahan kimia seperti DDE dan DDT pada pestisida yang telah terbukti bersifat karsinogenik dan masih digunakan di Indonesia. Paparan bahan kimia dari bahan kimia rumah tangga seperti PCB, Benzophenone, dan Phthalates di beberapa peralatan rumah tangga juga merupakan zat karsinogenik. Penggunaan BPA, BaP, dan 2-Amino-1-Methyl-6-Phenylimidazo[4,5-B]pyridine dalam kemasan makanan memicu terjadinya kanker payudara. Paparan asap rokok atau perilaku merokok, konsumsi dan penguapan alkohol, serta paparan PM2.5 merupakan polutan udara yang berisiko menyebabkan kanker payudara. Cara mencegahnya, kita bisa menggunakan biopestisida, bioplastik, mengubah gaya hidup sehat dan mengganti bahan bakar fosil menjadi biofuel.